Evaluation of employee assistance programme in the National Prosecuting Authority with special reference to Capricorn District in Limpopo Province - Mahlatjie, Tebogo Madiane Anna (University of Limpopo, 2016)
This dissertation on the Evaluation of an Employee Assistance Programme determines the worth or value of the programme by assessing its effectiveness or ineffectiveness. It also seeks to determine if the target population was reached. This study evaluates the level of EAP awareness and utilization by prosecutors. It also focuses on the effectiveness of the programme in addressing their work and personal challenges. It further seeks to understand the level of referring prosecutors to the EAP by their supervisors. The study is evaluative in design and is based on evaluation theory. The population of the study comprises 31 prosecutors from all three Magistrate complexes within Capricorn District (Limpopo Province), namely, Mankweng, Polokwane and Seshego. The total number of prosecutors reached is 31. Data were collected through questionnaires from all the respondents. The study collected information on absenteeism, sick leave and disciplinary matters in order to measure EAP utilisation before and after the programme was introduced to employees. The wish was not successful because the Human Resources system utilised within the NPA did not capture such information as anticipated. The main findings of the study are that prosecutors are aware of the Employee Assistance Programme and most respondents who used the EAP referred themselves. It is clear that prosecutors are aware of the benefits obtained from the programme. Even though a large number of prosecutors were aware of the existence as well as the services offered by the EAP within the NPA, the utilisation rate of the programme was low. The other major finding is that the EAP within the NPA is underutilised. Lastly, the EAP within the NPA in Capricorn District, Limpopo Province is not effective in addressing prosecutors’ work and personal problems.
Thesis (M. A. (Social Work)) -- University of Limpopo, 2016
Keywords: Employee assistance programs; National Prosecuting Authority; Limpopo Province; Employee assistance programmes; Personnel management